Solution synthesis and activation of spinel CuAl2O4 film for solar water-splitting - Tan, Runfa; Hwang, Sung Won; Sivanantham, Arumugam; Cho, In Sun (Journal of Catalysis, 2021)
We report a novel solution-processed copper-aluminate (CuAl2O4, CAO) film as a photocathode for photoelectrochemical water-splitting. Two types of CAO were synthesized, porous- and dense-CAO, with the controlled addition of polyvinylpyrrolidone. Importantly, we found that lithium-ion (Li+) incorporation onto CAO has profound effects. It simultaneously improves the light absorption, charge transport, and transfer properties. In particular, the bandgap value reduced from 1.9 to 1.5 eV. Additionally, the Li+-activated porous-CAO photocathode exhibited a water-reduction photocurrent density of −1.4 mA/cm2 at 0.4 V vs. the reversible hydrogen electrode (faradaic efficiency: ~ 70%) under simulated-sunlight illumination (100 mW/cm2), which is nine times higher than that of the pristine porous-CAO. Significantly, the photocurrent density of the Li+-activated porous-CAO photocathode further increased to −5.1 mA/cm2 by coupling with CuO underlayer, which is the highest value achieved among all the spinel-based-photocathodes. Our Li+ activation method can be extended to other spinel oxides, e.g., CuBi2O4 and CuFe2O4, achieving over two times higher performance.
Keywords: Faradaic efficiencies; Photocurrent density; Photoelectrochemical water splitting; Poly vinyl pyrrolidone; Reversible hydrogen electrodes; Solar water splitting; Solution synthesis; Transfer properties; CuAl2O4; Lithium-ion incorporation; Photocathode; Photoelectrochemical performance; Sol-gel synthesis